REGIONAL FREIGHT TRANSPORTATION MODEL FOR CRUDE PALM OIL IN CENTRAL KALIMANTAN - Noor Mahmudah; Siti Malkhamah; Danang Parikesit; Sigit Priyanto (Jurnal Transportasi, 2010)
This study attempts to model freight transportation of specific commodity in the regional scale, particularly to identify the shortest route of Crude Palm Oil (CPO) commodities, which are transported from factories to ports using different transportation network and mode. Several activities were performed, includingidentifying the location of palm plantations and factories supporting CPO industries, identifying intermediate points in the road and river networks, and determining the access route of CPO transportation from factory to the road or river networks. In determining the shortest route, various transportation networks and modes are simulated using Geographical Information System analysis by considering travel distance, time, and costas the variables influencing transportation systems. There are 113 of CPO factories identified, then be classified into three classes by considering their production capacity. It is found that 80 factories are classified as small (71%), 26 factories are medium (23%), and 7 factories are big (6%). The shortest route is identified through both road and river networks. The analysis of the shortest routes shows that road networks have shorter travel distance and time compared to the rivers. Nevertheless, river transportation offers a cheaper price compared to road transportation. Therefore, there is a competition between these two transportation modes, in which about 51% of factories probably use road networks and 49% use river networks. Moreover, it is predicted that about 70% of total CPO in Central Kalimantan is transported to Sampit port and only 30% is transported to Kumai port.Keywords: freight transportation, shortest route, Geographical Information System